Analysis of Corporate Social Responsibility at PT. Plantation X Based on the Perspective of "CSR Hierarchical Pyramid” - Fu'adah, Silvissifa'il; Sukoharsono, Eko Ganis (Basic and Applied Accounting Research Journal, 2024)
This study aims to analyze the implementation of CSR at PT Perkebunan Nusantara X (PTPN X) based on the CSR Hierarchical Pyramid perspective. This research is a qualitative library research with a case study approach. The data in this study are secondary data in the form of annual reports and sustainability reports of PTPN X for the 2020-2022 period collected through documentation. The results of this study indicate that (1) The results of the study indicate that almost all of PTPN X's CSR practices are in accordance with the CSR Hierarchical Pyramid which includes legal, economic, social philanthropy, environmental, and spiritual responsibilities. (2) PTPN X has fulfilled economic, environmental, and spiritual responsibilities (3) In legal responsibility, PTPN X has not disclosed the company's efforts to integrate with the customary laws of the community (4) In fulfilling social philanthropy responsibilities, gender equality indicators cannot be implemented optimally due to the inequality of employee gender ratios. Indicators of improving education and health quality have not been implemented consistently. (5) PTPN X has carried out spiritual responsibilities, this is reflected in policies and various activities based on policy values as God commands. (5) The results also prove that the concept of CSR Hierarchical Pyramid can be used as a model for implementing corporate CSR.